2021
DOI: 10.3390/s21113879
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Positioning and Accuracy Analysis Based on Real-Time Regional Ionospheric Correction Model

Abstract: As one of the main errors that affects Global Navigation Satellite System (GNSS) positioning accuracy, ionospheric delay also affects the improvement of smartphone positioning accuracy. The current ionospheric error correction model used in smartphones has a certain time delay and low accuracy, which is difficult to meet the needs of real-time positioning of smartphones. This article proposes a method to use the real-time regional ionospheric model retrieved from the regional Continuously Operating Reference S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…In E5a/L5 signals the differences found are greater with the smartphone presenting values in the order of 34 dBHz, while the Alloy presents values above 46 dBHz. Normally, the difference between a smartphone and a geodetic receiver in terms of SNR is around 10 dBHz, according to several studies presented by some authors (see Liu [10], Paziewski et al [25] and Liu et al [26]), the values of 8 and 12 dBHz in the E1/L1 and E5a/L5 bands, respectively, obtained by us are in agreement with a reference value. We also see that the smartphone's minimum values are below 20 dBHz, while the receiver values are above this value.…”
Section: Signal Qualitysupporting
confidence: 89%
See 1 more Smart Citation
“…In E5a/L5 signals the differences found are greater with the smartphone presenting values in the order of 34 dBHz, while the Alloy presents values above 46 dBHz. Normally, the difference between a smartphone and a geodetic receiver in terms of SNR is around 10 dBHz, according to several studies presented by some authors (see Liu [10], Paziewski et al [25] and Liu et al [26]), the values of 8 and 12 dBHz in the E1/L1 and E5a/L5 bands, respectively, obtained by us are in agreement with a reference value. We also see that the smartphone's minimum values are below 20 dBHz, while the receiver values are above this value.…”
Section: Signal Qualitysupporting
confidence: 89%
“…Uradzi ński & Bakuła (2020) [8] showed, using a dual frequency smartphone, accuracies of 5 cm for GPS L1 solutions using a reference station a few kilometers away with a survey time of around one hour. Other authors developed works with smartphones with other proposes, Robustelli et al [9] had done experiments to assess the observations quality and performance of GNSS standalone positioning with dual frequency smartphones, while Liu et al [10] demonstrated the impact of real-time regional ionospheric correction model can have in the smartphone positioning and Sharma et al [11] analyzed the antenna limitations in a smartphone-based GNSS positioning approaches. The authors Zangenehnejad & Gao [12] recently published a work about the opportunities and perspectives that the use of GNSS smartphones can be employed in different types of applications in the areas of mapping, navigation, cadastral, and in a wide range of works with georeferencing needs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, DFRs are typically used for high-precision receivers, whereas single Frequency Receivers (SFRs) are usually utilized for mass-market GNSS receivers. Note that nowadays, dualfrequency support has been reported even in smartphones [38], yet it still does not concern the majority of smartphones today.…”
Section: Overview Of the Ionospheric Delay Conceptmentioning
confidence: 99%
“…Several things can explain this increased inaccuracy. First of all, there are many fluctuations and biases in the smartphone's components [38]. Secondly, dynamic conditions of Android-based measurements may suffer more errors compared to static acquisition.…”
Section: Data From Reference Stations-static Conditionsmentioning
confidence: 99%
“…Smartphone technology represents and includes portable computer-mediated communication technology (Yao and Ling 2020) that pertains to both the physical equipment and applicable software applications. Smartphones permit individuals to own a personal, hand-held computer for their unimpeded use (Yus 2021) in exchange for paying a monthly telecommunications fee to a service provider (Oh et al 2022), as well as for being within the range of a transmission tower (Gopi et al 2023) operated by a server-specific satellite (Liu et al 2021). Unless users reveal personal information about themselves, other users may be unable to tell the age of a smartphone user.…”
Section: Introductionmentioning
confidence: 99%